PENINGKATAN TPACK GURU MATEMATIKA SMK MELALUI PELATIHAN DAN PENDAMPINGAN PEMBUATAN MEDIA PEMBELAJARAN DIGITAL (CANVA DAN MATHCITYMAP) - Fauzi, Moch.; Prasetyo, Puguh Wahyu; Shodiq, Lukman Jakfar; Triayuningtiyas, Alfika; Nandika, Fuja Dwi (Abdi Panca Marga, 2024)
The majority of vocational mathematics teachers in Lumajang region provide mathematics materials traditionally using textbooks as learning resources. Whereas the fast development of technology can support the improvement of teachers' Technological Pedagogical Content Knowledge (TPACK). The use of technology such as Canva and Mathcitymap applications makes teaching materials look better, real, and more attractive. It was necessary to improve teachers' soft skills in mastering the Canva and Mathcitymap applications so that their skills in integrating technology in mathematics learning materials also increased. The implementation of this project uses training and mentoring methods for service partners, namely members of the MGMP of vocational mathematics teachers of Lumajang Regency in the odd semester of 2023/2024. Training was conducted online through zoom meetings and mentoring was carried out directly to selected teachers to practice the use of Canva and Mathcitymap. The results of the program showed an increase in mastery the concept of "Canva as an interactive math learning media" at 84.7%, an increase in mastery of the concept of "Mathcitymap" as a learning support application at 80.3%, and an increase in teachers' TPACK in making digital math learning media at 84%. This high increase in skills and knowledge needs to be balanced with the availability of digital facilities and infrastructure at school, which is the main obstacle faced by teachers at this time. In addition, teachers also expect further training on digital-based assessment in differentiated learning. References Adawiyah, R., Amin, S. M., Ibrahim, M., & Hartatik, S. (2021). Peningkatan ketuntasan hasil belajar siswa sekolah dasar pada pembelajaran tematik melalui E-LKPD dengan bantuan aplikasi Google Meet. Jurnal Basicedu, 5(5), 3393–3398. Cahyono, A. N., & Ludwig, M. (2016). MathCityMap: Exploring mathematics around the city. 13th International Congress on Mathematics Education (ICME-13), Hamburg. Cahyono, A. N., Ludwig, M., & Marée, S. (2015). Designing mathematical outdoor tasks for the implementation of The MathCityMap-Project in Indonesia. In Pursuit of Quality Mathematics Education for All: Proceedings of the 7th ICMI-East Asia Regional Conference on Mathematics Education, 151–158. Dewi, R., Budiarti, R. S., & Aina, M. (2017). Pengembangan lembar kegiatan peserta didik (lkpd) bermuatan pendidikan karakter dengan model pembelajaran guided inquiry pada materi bakteri bagi siswa kelas x sekolah menengah atas. Biodik, 3(1), 17–26. Fauzi, M., & Shodiq, L. J. (2022). Development of learning media microsoft powerpoint based on visual basic for application (VBA). AIP Conference Proceedings, 2577(1), 20011. Hartanto, D., Prasetyo, P. W., Maryani, I., Maharani, E. A., Puspitasari, I., Putri, D. A., Aji, O. R., & Purwanto, W. E. (2020). Developing digital module for human literacy and technology literacy. International Journal on Education Insight, 1(1), 29–40. Hasibuan, I. (2015). Hasil Belajar Siswa pada Materi Bentuk Aljabar di Kelas VII SMP Negeri 1 Banda Aceh Tahun Pelajaran 2013/2014. Jurnal Peluang, 4(1), 5–11. Hidayah, I., & Istiandaru, A. (2018). Manipulatives and Question Series for Elementary School Mathematics Teaching on Solid Geometry. International Journal of Instruction, 11(3), 649–662. MathCityMap. (2023). Tutorials. https://mathcitymap.eu/en/tutorials-en/ Peni, N. R. N., Sumargiyani, S., & Prasetyo, P. W. (2022). Pemanfaatan Canva dalam Pembuatan Soal HOTs Studi Kasus SD Muhammadiyah Bogor. Prosiding Seminar Nasional Hasil Pengabdian Kepada Masyarakat Universitas Ahmad Dahlan, 4(1), 567–574. Prasetyo, P. W., Setyawan, F., & Suyitno, H. (2023). Pembelajaran berbasis pendidikan karakter untuk meminimalkan learning loss akibat pandemi dengan implementasi aplikasi, mathcitymap di Sekolah Indonesia Bangkok dan Davao. Prosiding Seminar Nasional Hasil Pengabdian Kepada Masyarakat Universitas Ahmad Dahlan, 4(1), 811–821. Rahmatillah, R., Halim, A., & Hasan, M. (2017). Pengembangan lembar kerja peserta didik berbasis keterampilan proses sains terhadap aktivitas pada materi koloid. Jurnal IPA & Pembelajaran IPA, 1(2), 121–130. Rahmatullah, R., Inanna, I., & Ampa, A. T. (2020). Media pembelajaran audio visual berbasis aplikasi canva. Jurnal Pendidikan Ekonomi Undiksha, 12(2), 317–327. Sulistyorini, S., & Harmanto, Z. A. (2018). Pengembangan lembar kerja peserta didik (LKPD) tematik terpadu mengintegrasikan penguatan pendidikan karakter (PPK) dan literasi siswa SD Di Kota Semarang. Jurnal Kreatif: Jurnal Kependidikan Dasar, 9(1)